All-in-one stretchable coaxial-fiber strain sensor integrated with high-performing supercapacitor - Pan, Z. (2021)
Ever-increasing attempts have recently been focused on exploring stretchable fiber-shaped integrated wearables, owing to their multi-functionalities and mechanical flexibilities. However, a rational design and effective integration of multi-functional components, such as strain sensor and high-performing energy storage, into one single fiber remains a great challenge. Herein, we have achieved an all-in-one stretchable coaxial-fiber sensing system simultaneously integrating strain detection and power supporting supercapacitor. The asymmetric stretchable coaxial-fiber supercapacitor is made on an elastic fiber, with a maximum working voltage of 1.8 V, by adopting manganese dioxide and polypyrrole deposited on aligned carbon nanotube sheets as the positive and negative electrode, respectively. Benefiting from the unique coaxial-fiber integrated architecture and advanced electrode design, the optimized device delivers a high stack volumetric energy density of 1.42 mWh cm−3, and an outstanding flexibility with 85.1% capacitance retention after stretching for 6000 cycles at a strain of 200%. The all-in-one stretchable coaxial-fiber strain sensing system shows consistent self-supported performance with a superior stability and durability at repeatedly unloading/loading of 40% applied strain for 10000 cycles, after one single charge. The present work demonstrates the new proof-of-concept for integration of strain element with energy storage into a single stretchable fiber for the next generation wearables.